Bio-Guided Isolation of Acetogenins from Annona cherimola Deciduous Leaves: Production of Nanocarriers to Boost the Bioavailability Properties - Maria Teresa Gutiérrez; Alexandra G. Durán; Francisco J. R. Mejías; José M. G. Molinillo; Diego Megias; Manuel M. Valdivia; Francisco A. Macías (Molecules, 2020)
Annonaceous acetogenins (ACGs) are lipophilic polyketides isolated exclusively from Annonaceae. They are considered to be amongst the most potent antitumor compounds. Nevertheless, their applications are limited by their poor solubility. The isolation of ACGs from Annona cherimola leaves, an agricultural waste, has not been reported to date. Molvizarin (1) cherimolin-1 (2), motrilin (3), annonacin (4) and annonisin (5) are isolated for the first time from A. cherimola deciduous leaves. Annonacin was found to be four- and two-times more potent in tumoral cells (HeLa, 23.6% live cells; IGROV-1, 40.8% live cells for 24 h) than in HEK-293 at 50 µM (24 h, 87.2% live cells). Supramolecular polymer micelles (SMPMs) were synthesized to encapsulate the major ACG isolated, annonacin, in order to improve its solubility in aqueous media. The bioavailability of this compound was increased by a factor of 13 in a simulated human digestive system when compared with free annonacin and an encapsulation efficiency of 35% was achieved. In addition, the cytotoxic activity of SMPMs that hosted annonacin (100 µM, 24 h, 5.8% live cells) was increased compared with free annonacin in water (100 µM, 24 h, 92% live cells). These results highlight the use of by-products of A. cherimola, and their pure compounds, as a promising source of anticancer agents. The use of SMPMs as nanocarriers of ACGs could be an alternative for their application in food field as nutraceutical to enhance the administration and efficacy.